KADER PENGGERAK: Upaya Pemberdayaan Kesejahteraan Keluarga di Kecamatan Pakis Kabupaten Magelang - Supriyadi Supriyadi (WELFARE : Jurnal Ilmu Kesejahteraan Sosial, 2019)
Women are a very productive source of labor in all fields. In this case village women tend to be housewives and their space to develop skills is very limited. Researchers aimed to determine the empowerment of cadres in the family welfare in the District of Pakis, Magelang Regency. This research is a qualitative research with a descriptive approach. The subjects of this study were the Head of the Banyusidi Village, the Driving Cadre of the Banyusidi Village. In collecting data researchers used the method of observation, interviews and documentation. While in the data analysis techniques researchers used data collection, data reduction, data presentation and drawing conclusions. The results showed that PKK Cadre Empowerment based on the theory of the empowerment process was divided into 5 stages namely Enabling, Empowering, Protecting, Supporting, and Fostering. Of the 5 stages the process has not been able to run optimally, especially in Enabling and Fostering. While the factors which become obstacles in empowering women through PKK come from members and also from the environment. While the supporters are strong encouragement from the board and the existence of support from outside the group.Keywords: Empowerment of women, PKK, Family Welfare